Technological Transformation and Challenges in Uzbekistan’s Journey Toward Marketing 5.0 - Musurmonov Otabek Sobirjon Ugli (Academia Open, 2025)
General Background: The evolution of marketing theory from Marketing 1.0 to Marketing 5.0 represents a global shift from product-centered strategies to technology-driven, human-centric marketing philosophies. Specific Background: In Uzbekistan, this transformation has occurred alongside rapid economic liberalization and digitalization, yet its pace and scope differ across industries. Knowledge Gap: While global literature extensively discusses Marketing 5.0, limited empirical research explores how developing economies like Uzbekistan adapt to this paradigm, particularly in balancing technological innovation with cultural and infrastructural constraints. Aims: This study investigates how Uzbek enterprises transition from traditional to technology-enabled marketing, focusing on challenges and enablers of adopting Marketing 5.0 practices. Results: Findings from qualitative case studies of leading companies—Artel, Beeline, UzAuto Motors, UZUM, and a textile SME—reveal an uneven progression, with large corporations advancing toward digital marketing integration while SMEs remain constrained by limited expertise, resources, and digital infrastructure. Novelty: The study provides one of the first localized analyses of Marketing 5.0 implementation in Central Asia, integrating cultural and organizational dimensions with technological readiness. Implications: The results underscore that successful marketing transformation in emerging markets requires not only technological investment but also policy support, digital education, and a balance between automation and human empathy. Highlights: Marketing in Uzbekistan is evolving from product-centered to technology-driven models. Large firms lead digital adoption, while SMEs face financial and skill barriers. Balancing technology with human empathy is crucial for sustainable marketing growth. Keywords: Marketing 5.0, Digital Transformation, Artificial Intelligence, Business Transformation, Emerging Economies